Edible Mushroom, an Ecosystem Service of Pine Forests (Pinus Radiata): A Study of the Communities Cuyuni and Yuracmayo (Cusco, Peru) - Córdova, Z.M. Díaz; Bravo-Toledo, L.A.; Tome-Ramos, C.O.; Cáceres-Paredes, J.; Vigo-Ingar, K.; García-Flores, S.; Valdivia-Zuta, J.; Pérez, N.E. Feijoo (International Journal of Membrane Science and Technology, 2023)
The present study aims to identify and quantify the edible mushroom with high production value in Pinus radiata forests, and their natural production as an ecosystem service for the peasant communities of Cuyuni and Yuracmayo in the district of Ccatca (Cusco, Peru). Fifty fungal samples were collected according to cap diameter (10 cm, 15 cm and 20 cm), for counting and taxonomic identification. The samples were collected in 5 Pinus radiata forests with different growth ages (forest younger than 3 years, between 4 to 7 years and older than 7 years). The edible fungal species identified were Laccaria laccata and Suillus luteus, both in symbiotic growth with Pinus radiata, the latter being the most representative species due to its abundance and usefulness food, which gives it a high commercial value. The non-parametric Kruskal-Wallis test of SPSS software was used and determined that there is a statistical difference between different groups of the Suillus luteus and Pinus radiata forests with different growth ages. For example, it presents a higher average growth rate in Pinus radiata forests older than 7 years with an average production rate of 523.6 kg in fresh weight per harvesting season. However, there is also a homogeneity of the Suillus luteus species in all the Pinus radiata forests. Therefore, this type of fungus represents the most productive edible mushroom component for the Cuyuni and Yuracmayo communities.